2018
DOI: 10.1038/s41467-018-07666-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage cells secrete factors including LRP1 that orchestrate the rejuvenation of bone repair in mice

Abstract: The pace of repair declines with age and, while exposure to a young circulation can rejuvenate fracture repair, the cell types and factors responsible for rejuvenation are unknown. Here we report that young macrophage cells produce factors that promote osteoblast differentiation of old bone marrow stromal cells. Heterochronic parabiosis exploiting young mice in which macrophages can be depleted and fractionated bone marrow transplantation experiments show that young macrophages rejuvenate fracture repair, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 65 publications
5
89
0
1
Order By: Relevance
“…Mice (aged ~12 weeks) were irradiated (900 cGy) and the tail vein injected with bone marrow isolated from age-matched donors (1 × 10 6 cells in 200 ml PBS). Engraftment into the bone marrow was allowed to occur for 2 months and verified using flow cytometry as previously described 36 .…”
Section: Parabiosismentioning
confidence: 99%
“…Mice (aged ~12 weeks) were irradiated (900 cGy) and the tail vein injected with bone marrow isolated from age-matched donors (1 × 10 6 cells in 200 ml PBS). Engraftment into the bone marrow was allowed to occur for 2 months and verified using flow cytometry as previously described 36 .…”
Section: Parabiosismentioning
confidence: 99%
“…Data available in the literature indicate multiple functions for macrophages during bone regeneration. Recently, the supportive function of F4/80 + macrophages during bone regeneration via enhanced osteogenesis when transplanted to aged individuals was demonstrated (46). In addition, it is known that F4/80 + osteomacs support osteoblast function (47).…”
Section: Discussionmentioning
confidence: 99%
“…Its role in influencing the differentiation of mesenchymal stem cells is still unclear [ 97 ]. Besides, the low-density lipoprotein receptor-related protein 1 (Lrp1) produced by young macrophage plays a role in bone homoeostasis, osteoblast function and even rejuvenate fracture repair in old mice [ 98 ]. Fu and co-workers reported that CCL3 inhibited osteoblast function and suppressed proliferation and osteogenic potential of osteoblasts in patients with myeloma bone disease.…”
Section: The Pivotal Roles Of Macrophages In Bone Regenerationmentioning
confidence: 99%